Premature senescence of endothelial cells upon chronic exposure to TNFα can be prevented by N-acetyl cysteine and plumericin - Khan, Shafaat Y. (Sci Rep, 2017)
Cellular senescence is characterized by a permanent cell-cycle arrest and a pro-inflammatory secretory phenotype, and can be induced by a variety of stimuli, including ionizing radiation, oxidative stress, and inflammation. In endothelial cells, this phenomenon might contribute to vascular disease. Plasma levels of the inflammatory cytokine tumor necrosis factor alpha (TNFα) are increased in age-related and chronic conditions such as atherosclerosis, rheumatoid arthritis, psoriasis, and Crohn’s disease. Although TNFα is a known activator of the central inflammatory mediator NF-κB, and can induce the intracellular generation of reactive oxygen species (ROS), the question whether TNFα can induce senescence has not been answered conclusively. Here, we investigated the effect of prolonged TNFα exposure on the fate of endothelial cells and found that such treatment induced premature senescence. Induction of endothelial senescence was prevented by the anti-oxidant N-acetyl cysteine, as well as by plumericin and PHA-408, inhibitors of the NF-κB pathway. Our results indicated that prolonged TNFα exposure could have detrimental consequences to endothelial cells by causing senescence and, therefore, chronically increased TNFα levels might possibly contribute to the pathology of chronic inflammatory diseases by driving premature endothelial senescence.